The prodigal peptides - Sanjay Kalra; Atul Dhingra; Suneet Kumar Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
The identification and isolation of newer hormones and transmitters has helped establish and expand the field of gastrointestinal endocrinology.1 Our understanding of these molecules, and their receptors, has allowed us to unlock their therapeutic potential as well. Agonists of these peptides are now used as treatment for type 2 diabetes and obesity, as well as prophylaxis to reduce adverse cardiovascular and metabolic outcomes.2 Their development has enhanced the relevance of peptide pharmacology from an insulin-centric industry to a dynamic multipeptidic discipline. Various peptides, discovered over the past few decades, are now being evaluated for their diagnostic and therapeutic potential. We term these the prodigal peptides. Based upon the Biblical parable of the prodigal son, we use this description to highlight the “coming of age” of these hormones.